Andrea del Sarto - Natali, Antonio 1951- (Abbeville, 1999)
"The most important painter working in Florence when Raphael and Michelangelo were active in Rome, Andrea del Sarto (1486-1530) was a master of tone and color, the teacher of Pontormo, Rosso, Vasari, and other Mannerists. In this monograph illustrated with almost 200 reproductions, Antonio Natali reviews Andrea's art and life, proposing a new understanding of the man and the poetics of his paintings."--BOOK JACKET.